Quantitative Approaches for the Student-Managed Investment Fund - Bai, Qing; Bustle, Nicholas Francis; Lyu, Fangyu (My University, 2017)
We examined the performance of a total of six quantitative strategies over three, five, and ten years horizons. We are presenting the two strategies with the best results. To begin, we first define what Student Managed Investment Fund and Smart Beta investment strategies are and why they are important. We hypothesized that it would be possible to implement Smart Beta strategies for our Student Managed Investment Fund for the purpose of gaining a better than market return on our investment and give students the opportunity to learn and invest outside of the academic field.
Color poster with text, charts, and graphs.
Keywords: Student managed investment fund; Smart beta strategies; Stock price indexes; Posters